Glycan-based nanocarriers in drug delivery - (:unkn) unknown (Apple Academic Press, 2017)
Glycans are linear or branched polymer molecules composed of repeating sugar units adjoined by glycosidic bonds. Next to DNA and protein, glycans are considered as the third dimension in molecular biology and various properties of glycans such as biocompatibility, solubility, potential for modification, and innate bioactivity offer great potential for their use in drug delivery systems (DDS). Hence, recently, studies on glycans and their applications as nanoparticle drug delivery systems are accelerated. In this chapter, after a brief introduction to glycans and glycan-based DDS, various glycans including chitosan, hyaluronic acid, alginate, dextran, hydroxyethyl starch, levan and mannan that are used in drug delivery are summarized and finally their role as nanocarriers in DDS are discussed. © 2018 by Apple Academic Press, Inc.
Keywords: Drug delivery systems; Glycan; Glycotechnology; Nanocarriers; Nanoparticles; Polysaccharides